Emergency Preparedness, Resilience and Response (EPRR). Issue 1 (23rd August 2018) - Quantick, Oliver
Abstract : As an organisation, locality or nation, there is a growing need to respond to a wide range of incidents and emergencies that could affect health and the care of patients. Responses to both domestic and international incidents have shown that collaboration, understanding and joint responses across organisations have improved the outcome of those affected by incidents which impact on health. Emergency response is something that is of increasing importance and has been tested on multiple occasions during recent events in the UK. Regarding health, the aim is to respond rapidly and efficiently, reducing potential morbidity and mortality to the lowest possible level in a given circumstance. This paper discusses what is meant by EPRR (Emergency, Preparedness, Resilience and Response), types of potential incidents, how we collectively prepare for responding and what has been learnt during recent events. It concludes with an outline of some selected current activity and highlights the likelihood of increased cross-sector working in EPRR.